Magnesium Phosphate Cements formulated with a low-grade MgO by-product: Physico-mechanical and durability aspects. (30th August 2015) - Formosa, J.; Lacasta, A.M.; Navarro, A.; del Valle-Zermeño, R.; Niubó, M.; Rosell, J.R.; Chimenos, J.M.
Highlights: MPC formulated with LG-MgO by-product were selected from preliminary study. Evaluation as repairing mortar: adhesion and MOE tests. Durability studies evaluating the porosity and sorptivity prior and post-aging. MPCs formulated with LG-MgO by-product show good durability and repairing properties. Abstract: Chemically Bonded Phosphate Ceramics (CBPCs) and, in particular, Magnesium Phosphate Cements (MPCs), show properties very adequate for using as repair mortar for concrete constructions. The obtainment of MPC using MgO-containing by-products as raw materials was proposed by the authors in previous works. There, formulations including boric acid as additive were optimized to obtain good mechanical properties and proper setting times. The current study aims to analyze the viability of the developed formulations to be used as repair mortar. Adhesion to concrete surfaces was evaluated, and in all cases good adhesion strength values were obtained. The durability tests, including freeze/thaw cycles and salts crystallization cycles, have shown an excellent behavior, especially the samples containing the higher amount of boric acid. These promising results indicate that MPC formulated with a low-cost MgO by-product can be an interesting alternative to other repair mortars. In addition to economic benefits in terms of cost of production, the use of by-products has a positive impact on environmental and sustainability aspects.